CHARACTERISTICS OF CHILD-FRIENDLY SCHOOLS TO PREVENT VIOLENCE (CASE STUDY IN SDI AL ZAHRA INDONESIA) - Fidrayani Fidrayani (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2023)
Abstract. This study aims to describe the characteristics of child-friendly schools at SD Al Zahra Indonesia to prevent violence. With a qualitative approach with an observation method by the instruments that have been prepared. From several indicators, it can be concluded that has qualified as a child-friendly school, although it has not been officially launched. It is hoped that the fulfilment of these indicators will reduce the impact of violence on children in schools. The development of child-friendly schools can be applied to all levels of education, especially in basic education.